O tombamento do patrimônio cultural carioca: estudo de caso sobre as “calçadas musicais” de Vila Isabel - Couto, Jéssica Santos Sé Prado (2019)
Vila Isabel is a traditional neighborhood known for its culture and history. Because of its cultural heritage, in 1964 a cobblestone pavement of Portuguese stones was built at Boulevard 28 de Setembro which paves the connection of the neighborhood with samba. This sidewalk is “tombada” by the law n ° 2,790 of April 27, 1999. The objective of this paper is to understand how the “tombamento” occurs through the laws, analyzing how the process is operated in the federal, state, municipal spheres and if it is effective at the present time.